2000
DOI: 10.1029/1999wr900289
|View full text |Cite
|
Sign up to set email alerts
|

Glass casts of rock fracture surfaces: A new tool for studying flow and transport

Abstract: Abstract. A method was developed for fabricating transparent glass casts of fractured rock pairs. These glass casts provide reproduction of surface topography and roughness of natural fractures, optical clarity, and representative wettabilities of mineral surfaces. The glass casts are an improved tool for studying flow and transport in fractures compared to previous approaches. The surface of a clean glass fracture has a contact angle near zero, and more importantly, the surface wettability can be intentionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In the case study, an important feature that merits additional analysis is the fundamental difference between the carried out studies on single fractures (Kumar et al, 1995;Yeo et al, 1998;Wan et al, 2000) in which Taylor dispersion was found to occur and the dominance of geometric dispersion in our complex fracture network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case study, an important feature that merits additional analysis is the fundamental difference between the carried out studies on single fractures (Kumar et al, 1995;Yeo et al, 1998;Wan et al, 2000) in which Taylor dispersion was found to occur and the dominance of geometric dispersion in our complex fracture network.…”
Section: Discussionmentioning
confidence: 99%
“…In the case study, due to the complex, tortuous topology of the fracture network there may not be an opportunity for Aris-Taylor dispersion to develop. The obtained results need to be compared with previous studies carried out in limestone, granite and welded tuff fractures (Kumar et al, 1995;Yeo et al, 1998;Wan et al, 2000) that found the dominance of Aris-Taylor dispersion. The previously reported experiments (Detwiler et al, 2000) regard a single fracture in which the fraction of contact area between the fracture surfaces was relatively small.…”
Section: Solute Transportmentioning
confidence: 99%
“…1). The transparent glass casts are particularly useful for a visual and quantitative study of multiphase flow in rock fractures (Wan et al, 2000). The mean aperture of the fracture was 760 mm, and one fracture pore volume (PV) was estimated from the product of the mean aperture and the projected fracture area, leading to a 1 PV of 19.136 ml (Fig.…”
Section: Fracture and Remedial Fluidsmentioning
confidence: 99%
“…They are often associated with unpredictability and variability 2 . Decades of studies, ranging from single narrow fractures dominating flow 3 , to wells or drawdowns in a fractured formation (4)(5) revealed many fundamental features of structural geology, and hydrogeology. Emphasis has been given to understanding of fracture geometry 1 , new techniques for conductive fracture detection (6)(7) , and new tools for computer simulation 8 .…”
Section: Introductionmentioning
confidence: 99%